Heritage Marketing and City Branding: Positioning Lasem as a Living Heritage City - Nur Endah Retno Wuryandari; Setiyo Purwanto; Achmad Sudiro; Kusuma Ratnawati (Lembaga Publikasi Ilmiah Nusantara, 2026)
Lasem has valuable cultural heritage assets, especially its batik traditions, urban history, and multicultural identity; however, these resources have not yet been fully developed into a heritage-based city branding strategy. This study examines how Heritage Marketing can enhance Lasem's promotion as a Cultural Heritage Town in line with the Sustainable Development Goals (SDGs). Using a qualitative case study approach, the research includes in-depth interviews, visual and textual documentation, and thematic analysis of narratives created by batik entrepreneurs and local heritage stakeholders. The findings highlight four key issues. First, Lasem has significant heritage assets linked to batik motifs, collective memory, historical narratives, and community-driven cultural practices. Second, there is a major challenge in effectively translating these assets into clear city narratives and market communications. Third, digitalization and AI tools offer significant opportunities to enhance the visibility of these heritage elements through storytelling, visual content, and social media marketing. Fourth, the success of digital promotion relies on maintaining cultural authenticity, especially regarding the original motifs, colors, and meanings of Batik Lasem. This article offers a conceptual model that connects heritage assets, cultural storytelling, digital activation, collaboration among various actors, and sustainable city branding, advancing heritage-focused urban marketing and culturally rooted local development.